The Result of an Analysis on the relationship between Mindfulness and Cycling - Chatchawanwan, Yuttapong (Journal of International Buddhist Studies, 2018)
This study attempts to analyze the result of the relationship between cycling and mindfulness practice. While human being is fully occupied and has limited time joining meditation in the temple, applying sport exercised in routine’s daily life became another choice in order to be mindful. This study applied qualitative method by analyze former sport science researches that related to benefits of mindfulness practice. The findings show that cycling exercising benefits to physical body and mind. The observation of bodily sensations during exercising implied to be efficient mindfulness practice that is useful for living life. The blending of Buddhist fundamental and sport science theory generated particular benefits improving physical and mental health development as well as being an effective modern therapy in order to cure psychological patience. Mindfulness training during exercise leads to health development consecutively. The concentration perceives the changing of mind and physical sensation reducing tension, violence, and anger acknowledgement, anxiety efficiency management. Mindfulness practice increases tolerance and understanding of difficult situations and helping people to take appropriate decisions and action by increasing constructive activity and work efficiency. Understanding law of nature, happiness or mind suffering, comfortable or painful physical body, all states always has the same characteristic which is arising and passing away. Things are impermanence. These particular method is an effective towards the wisdom.